Automotive market: does corporate brand reputation and brand authenticity lead to brand attachment? - Bellégo, Goulwen Le (2017)
The evolution of the automotive market since its beginning changed drivers’ life in multiple ways. Technologies evolution allow cars manufacturers to update there models and make them continuously safer, easier to drive and respectful of the environment. The automotive market is composed of numerous manufacturers form everywhere in the world, leaded by some well-known groups as Volkswagen from Germany, Toyota from Japan, or General Motors from U.S.A. Therefore, cars companies fight hard to get more customers driving and enjoying their vehicles. In the middle of all those vehicles how do consumer behaviour is analysed by marketers to attract them into a specific brand, does corporate brand reputation or brand authenticity lead to brand attachment? Empirical evidence based on data collected from the inquiry applied to a sample composed by 327 owners and drivers of Tesla, Toyota and Volvo cars, suggests that automotive market’s customers are mostly influenced by the authenticity of the car brand rather than by its corporate reputation. Thus, customers in general tends to have more attachment toward a brand that has a good ‘level’ of authenticity. The present research adapted several variables as customer sentiment and relationship toward a brand, as well as corporate brand reputation, brand attachment and brand authenticity. Also the sample used for the inquiry was segmented following next variables: Age, Gender, Household situation, Job Position & Living Area. Considering that there are not many studies & research developed around the automotive market when brand attachment construct is used, also when three single brand are compared and analysed each others on the same scale. Thus this study aim to give new insights into the automotive market, more precisely, on how do customers get attached to a specific brand.